Design of A Microchip Optical Switching Driven by Low Direct-current Voltage - Dedi Irawan (IAES Indonesia Section, 2017)
A microchip optical switching based on a directional fiber coupler has been successfully fabricated by using silicon-on-insulator with two steps of photolithography and dry etching methods. Each waveguide has 1.75 µm width, 2 µm high and the distance between the waveguides at the coupling region was 2 µm. Metal aluminum layer with 4 µm width was attached at the coupling region due to switch the optical signal from a waveguide to another. The coupled mode theory was determined to model the coupling power at the coupling region. Experimental results have shown a good agreement of switching power at the coupling as function of increment of direct current voltage. It has been obtained that to switch the signal described by the switching region that occurs for the applied DC voltage in range of 18 volt to 32 volt. Certainly, an adjustable optical switching driven by low direct current voltage promises wide range of its application in optical network and sensor application.